The Influence of Facilities and Service Quality on Member Satisfaction of The Golden Stik Kelapa Dua Depok Gym - Rosiyan, Dinu; Nurranto, heri; Mursito, Hardian; Lestiyono, Sidik (PT. Maju Malaqbi Makkarana, 2024)
This research aims to analyze the influence of facilities and service quality on member satisfaction at the Golden Stik Kelapa Dua Depok Gym. In the fitness industry, member satisfaction is an important factor that determines the success and sustainability of a fitness center. This research uses quantitative methods with a survey involving a number of Golden Stik Gym members as respondents. The data collected was analyzed using statistical techniques to determine the influence of facilities and service quality on member satisfaction. The research results show that both facilities and service quality have a significant influence on member satisfaction. Complete and high-quality facilities, such as modern equipment, maintained cleanliness and comfortable spaces, contribute positively to member satisfaction. Apart from that, service quality, which includes staff professionalism, responsiveness to member needs, and the ability to provide personalized service, has also been proven to have a big impact. This research provides valuable insight for Golden Stik Gym management in their efforts to increase member satisfaction. In addition, the results of this research can be used as a reference for other fitness centers in developing strategies to increase their member satisfaction and loyalty. With the right focus on improving facilities and services, it is hoped that fitness centers can meet member expectations and continue to grow in this competitive industry